CHALLENGES OF THE HEALTH SECTOR AND POPULATION AGING IN CUBA: ETHICAL AND POLITICAL STAKES - DESTREMAU, Blandine (MEDECINE LEGALE DROIT MEDICAL, 2025)
The development of health services in Cuba has been grounded in specific social and political ethics, embedded in the Revolutionary goals of social justice. Their performances are remarkable and widely documented, but they have been undergoing a series of economic and socio-demographic challenges. In a context of strong fiscal constraints, aging represent an ordeal which, beyond mere health stakes, raises issues of intergenerational justice and that of the sustainability of equalitarian achievements of social policies.